PERBANDINGAN STORE IMAGE DAN STORE ATMOSPHERE PADA TOKO PELANGI STATIONERY DAN TOKO MM RIZKY ABADI STATIONERY - Eva Khurrotul Ainiyah; Ayu Nur Khasanah (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study research to analyze the comparison of store image and store atmosphere at Pelangi Stationery Store and Mm Rizky Abadi Stationery Store. This research was carried out by distributing it to 35 consumers of Pelangi Stationery Store consumers and 35 respondents of MM Rizky Abadi Stationery Store. The analysis technique used is a quantitative analysis technique with the Independent sample T-Test analysis method. The results of this study show that there is no comparison or significant difference to the Store Image of Pelangi Stationery Store and MM Rizki Abadi Stationery Store and there is no significant comparison or difference to the Store Atmosphere of Pelangi Stationery Store and MM Rizki Abadi Stationery Store.